2011
DOI: 10.1002/adem.201100082
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Mechanical Properties of Reticulated Titanium Scrolls

Abstract: Titanium and its alloys find widespread use in skeletal implants and biomedical devices (e.g., stents and orthodontic applications) owing to their excellent corrosion resistance, bio-compatibility, static and fatigue strength, and lack of magnetism (an important property for magnetic imaging). [1] Microporous titanium provides two additional advantages for implant applications: first, it reduces the stiffness of the material, thus reducing stress shielding, [2,3] and, second, it improves implant anchorage by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 37 publications
(10 citation statements)
references
References 38 publications
1
9
0
Order By: Relevance
“…Similar to previously described inks, 2D sheets comprised of several layers can be created and manipulated via rolling, folding (origami), cutting, folding and cutting (kirigami), and fusing ( Figure A). However, unlike previously described inks, these sheets can be rapidly produced (Video S2, Supporting Information), handled immediately, and manipulated as long as one year after fabrication, without needing to rewet with solvent to impart flexibility.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to previously described inks, 2D sheets comprised of several layers can be created and manipulated via rolling, folding (origami), cutting, folding and cutting (kirigami), and fusing ( Figure A). However, unlike previously described inks, these sheets can be rapidly produced (Video S2, Supporting Information), handled immediately, and manipulated as long as one year after fabrication, without needing to rewet with solvent to impart flexibility.…”
Section: Resultsmentioning
confidence: 99%
“…The result is an architecture comprised of struts consisting of polymer‐bound powder. Ahn et al previously demonstrated that liquid‐based TiH 2 ink suspensions, could be printed into 2D sheets, which, after wetting with solvents, could be folded and otherwise manipulated to create 3D TiH 2 objects which could be thermally decomposed to create partially sintered titanium metal . Although this process was successful, the authors noted that it was difficult to produce many layered, high‐aspect ratio objects, as well as unsupported, overhanging architectural features due to sagging of the inks under their own weight and lengthy solidification time.…”
Section: Introductionmentioning
confidence: 99%
“…We recently introduced a versatile and simple process for the additive manufacturing of cellular, metallic architectures, where a liquid ink, consisting of a suspension of metal oxide or metal particles, is first 3D‐printed into a structure, and this structure is then subjected to sintering, with an intermediate thermochemical reduction step if oxides are used . A similar direct ink writing approach has been used to produce reticulated sheets of TiH 2 that were then rolled or folded into scrolls or origami shapes and Ti–6Al–4V scaffolds for bone implants . Unlike established metal additive manufacturing methods (e.g., selective laser sintering or electron‐beam sintering or melting), our extrusion‐based method can be utilized to 3D‐print complex architectures comprised of many layers from an extensive range of materials (e.g., ceramics, metals, biologics) with no required drying time and with a single 3D‐printer at room temperature .…”
Section: Introductionmentioning
confidence: 99%
“…High‐throughput printing of functional materials in planar and three‐dimensional motifs would enable numerous applications, including autonomic materials with embedded microvascularization,1, 2 3D scaffolds for tissue engineering3 and cell culture,4, 5 lightweight structural composites,6–9 and printed electronics 10, 11. To date, direct laser12, 13 and ink‐writing methods14, 15 have been primarily used to produce small components (<1 cm 3 in volume), because lengthy fabrication times prohibit construction of larger structures.…”
mentioning
confidence: 99%
“…The resulting multilayer structure is composed of a 3D bicontinuous architecture (Figure 4b). This scalable approach could be extended to enable simultaneous printing of three or more arbitrary materials composed of viscoelastic polymer, ceramic, or metallic inks developed previously 1, 4, 6, 7, 11, 24…”
mentioning
confidence: 99%